Influence of temperature on anaerobic co-digestion process of organic solid waste. - MENEZES, J. M. C. (2013)
The process of anaerobic co-digestion (ACD) of organic solid vegetable waste (OSVW) with anaerobic sewage sludge (ASS) in the proportion of 80% and 20% (weight percent) respectively in anaerobic batch reactors (ABR), investigating the influence of temperatures at 25.5, 40.0 and 50.0 ºC, has been studied. The experimental system was composed of nine ABR with volumetric capacity of 1.15 liters each, of which 15 % of the total volume of each reactor was destined for the head-space. The reactors were monitored for the period of 160 days with weekly qualitative characterization, and daily quantification of the biogas produced. After completion of the monitoring period, the reactors were unloaded and the partially biostabilized waste was submitted to physico-chemical characterization, for the same parameters that were determined of the waste "in nature" used for loading the reactors. Among the conditions studied, it was observed that the best favored treatment by the ACD process was for the reactors monitored at 25.5 ºC, yielding total COD removal efficiency of 28.5%, volume of biogas accumulated 23.85 liters, volume of accumulated CH4 9.05 liters and maximum percentage of CH4 in biogas of 56%.